2018
DOI: 10.1093/mnras/sty1148
|View full text |Cite
|
Sign up to set email alerts
|

Approximations to galaxy star formation rate histories: properties and uses of two examples

Abstract: Galaxies evolve via a complex interaction of numerous different physical processes, scales and components. In spite of this, overall trends often appear. Simplified models for galaxy histories can be used to search for and capture such emergent trends, and thus to interpret and compare results of galaxy formation models to each other and to nature. Here, two approximations are applied to galaxy integrated star formation rate histories, drawn from a semi-analytic model grafted onto a dark matter simulation. Bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The four widely used parametric SFH models we consider (and some recent examples of their use in the literature) are: exponentially declining (Mortlock et al 2017;Wu et al 2018;McLure et al 2018), delayed exponentially declining (Ciesla et al 2017;Chevallard et al 2017), lognormal (Diemer et al 2017;Cohn 2018) and double power law (Ciesla et al 2017;Carnall et al 2018). For brevity we will refer to them as tau, delayed, lognormal and DPL models respectively.…”
Section: Parametric Sfh Modelsmentioning
confidence: 99%
“…The four widely used parametric SFH models we consider (and some recent examples of their use in the literature) are: exponentially declining (Mortlock et al 2017;Wu et al 2018;McLure et al 2018), delayed exponentially declining (Ciesla et al 2017;Chevallard et al 2017), lognormal (Diemer et al 2017;Cohn 2018) and double power law (Ciesla et al 2017;Carnall et al 2018). For brevity we will refer to them as tau, delayed, lognormal and DPL models respectively.…”
Section: Parametric Sfh Modelsmentioning
confidence: 99%
“…Extremely Randomised Trees (ERT; Geurts et al 2006) is one such ensemble approach that has been successfully used in a wide range of Astronomy domains (e.g. Kamdar et al 2016;Cohn 2018). It is similar to the popular Random Forest (RF): during training of a RF, a subset of K features is randomly chosen during each split, which reduces the correlation between trees where there are features with a strong correlation with the predictors.…”
Section: Extremely Randomised Treesmentioning
confidence: 99%
“…Diemer et al fitting SFHs using log-normals, found that the scatter in star formation histories could not be uniquely determined by a single parameter. Cohn (2018), building off of this work, compared Diemer et al (2017)'s log-normal model to one developed with PCA. Although PCA is able to reproduce simulated SFHs, the authors point out that the underlying assumption of PCA -that scatter seen in the simulation is but a deviation from a single underlying star formation history -is unlikely to be true.…”
Section: Introductionmentioning
confidence: 99%